2012
DOI: 10.1371/journal.pone.0045421
|View full text |Cite
|
Sign up to set email alerts
|

Globus Pallidus External Segment Neuron Classification in Freely Moving Rats: A Comparison to Primates

Abstract: Globus Pallidus external segment (GPe) neurons are well-characterized in behaving primates. Based on their firing properties, these neurons are commonly divided into two distinct groups: high frequency pausers (HFP) and low frequency bursters (LFB). However, no such characterization has been made for behaving rats. The current study characterizes and categorizes extracellularly recorded GPe neurons in freely moving rats, and compares these results to those obtained by extracellular recordings in behaving prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 47 publications
4
50
1
Order By: Relevance
“…1G). This is consistent with labeled Protos in awake mice (Dodson et al, 2015), and with the majority subpopulation in many GPe studies in awake monkeys and rats (DeLong, 1971; Raz et al, 2000; Gage et al, 2010; Benhamou et al, 2012). Identified Arkys were more irregularly active (Fig.…”
Section: Resultssupporting
confidence: 87%
“…1G). This is consistent with labeled Protos in awake mice (Dodson et al, 2015), and with the majority subpopulation in many GPe studies in awake monkeys and rats (DeLong, 1971; Raz et al, 2000; Gage et al, 2010; Benhamou et al, 2012). Identified Arkys were more irregularly active (Fig.…”
Section: Resultssupporting
confidence: 87%
“…In addition, the GPe receives dopaminergic inputs as well, although the functional significance of these inputs is not fully understood (Parent et al, 2001). Data collected from both rodent and primate studies indicate that a lower average firing rate has been observed in the rodent GP compared to the primate GPe, while firing patterns were very similar (Benhamou et al, 2012). The phMRI responses observed in the GPe following dopaminergic stimulations appear to parallel previously reported neurophysiological data.…”
Section: Discussionmentioning
confidence: 99%
“…Since FF and AF are sensitive to Poissonian noise and to across trial variability (Churchland et al, 2010), these metrics are able to detect local variations in pattern or rate. Two additional novel metrics, post spike suppression (PSP) (Benhamou et al, 2012) and residual metrics (Maimon and Assad, 2009) were also assessed, but were found to be not particularly useful. Because current metrics, including CV, LVr, and density histogram (Leblois et al, 2010), were found here to be inadequate for delineating burstiness, we developed a new burst discrimination metric.…”
Section: Introductionmentioning
confidence: 99%